QUESTIONS ON ACCOUNTING STANDARDS. - Littleton, A. C. (The Accounting Review, 1941)
Abstract The article focuses on questions on standards governing accounting. In an attempt to clarify some of the points raised by critics relating to accounting standards in the book, "An Introduction to Corporate Accounting Standards," the author has collected some questions from the correspondences and tried to answer them in his own views. To a question whether or not the phrase "measured consideration" is merely another way of saying money value and if there is any evidence to prove that the term "measured consideration" is more appropriate than the word "value" to indicate the subject matter of accounting, the author replies that he does not know of any evidence that could prove that one term was better than the other. He also comments that he is prejudiced against the use of the term "value" to indicate the subject matter of accounting. To a question why facts are more objective and verifiable now than they used to be before the author replies that modern complexities do seem to place difficulties in the path.